2021
DOI: 10.1111/acel.13340
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐conditioned medium attenuates the retinal pathology in amyloid‐β‐induced rat model of Alzheimer's disease: Underlying mechanisms

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This led to neuroprotection in the CNS, improving cell survival by inhibiting neuronal apoptosis, promoting cell proliferation, promoting cell regeneration, and preventing b amyloid deposition. ( Kuroda et al , 2020 ; Saha et al ., 2020 ; Kuo et al ., 2021 ; Park et al ., 2021 ; Alidous et al ., 2023 ) ( Fig. 7 ).…”
Section: Search Resultsmentioning
confidence: 99%
“…This led to neuroprotection in the CNS, improving cell survival by inhibiting neuronal apoptosis, promoting cell proliferation, promoting cell regeneration, and preventing b amyloid deposition. ( Kuroda et al , 2020 ; Saha et al ., 2020 ; Kuo et al ., 2021 ; Park et al ., 2021 ; Alidous et al ., 2023 ) ( Fig. 7 ).…”
Section: Search Resultsmentioning
confidence: 99%
“…An increasing body of evidence suggests that the Akt/GSK3β/β-catenin signaling pathway is essential in maintaining cell survival after ischemic retinal injury. 48 , 49 Enhanced phosphorylation at serine 473 in Akt reduced the neuronal death of experimental RIR mice, and inhibition of Akt phosphorylation promoted neuronal damage. 50 In the present study, we found that PGB significantly enhanced the phosphorylation of Akt following RIR.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, in a therapeutic perspective, effective overexpression of such essential neurotrophic factors is the key to curing the disease without causing severe and prolonged pathogenesis. Increased passage of MSCs naturally boost secretion of BDNF; MSCs are promising delivery systems for therapeutics in various neurodegenerative disorders, such as Alzheimer’s disease and Parkinson’s disease, because of their secretomes ( Rodrigues Hell et al, 2009 ; Harrell et al, 2021 ; Jalali et al, 2021 ; Kuo et al, 2021 ). Therefore, BDNF-MSCs could be effective in treating RTT, because of their ability to overexpress BDNF and the presence of neuroprotective or immunomodulatory exosomes.…”
Section: Discussionmentioning
confidence: 99%